Foster Care Liaisons in Higher Education: A Conceptual Framework for Supporting Post-secondary Success Among College Students with Experience in Foster Care. - Bustillos, Sheila; Norton, Christine Lynn; Tamplin, Elia (Child & Adolescent Social Work Journal, 2023)
Students with experience in foster care (SEFC) are an often overlooked student subgroup within the first-generation student population in higher education. The lack of attention on SEFC as a marginalized group in need of specialized support and guidance in higher education is the impetus for this study. In order to address this gap, the Texas Education Code (TEC) Section 51.9356 mandated all 2-year and 4-year state institutions in Texas accepting the tuition and fee waiver to have at least one university representative act as a foster care liaison. However, no guidelines were provided for what this role should include. Based on a pragmatic, problem-driven content analysis of documents from other states with similar roles, this study provides a theoretical rational and conceptual framework for foster care liaisons in higher education, including liaison expectations, training, and evaluation. The study concludes by examining future directions for practice, policy, and scholarship related to training and evaluating foster care liaisons in order to better support SEFC in higher education, and examines the role that social work can play in this process.